High Linearity And High Efficiency Cmos Power Amplifier And Up-conversion Mixer For 5g New Radio Sub-6 Ghz - Gunasegaran, Premmilaah (2024)
Fifth Generation (5G) New Radio (NR) is the latest wireless technology designed to meet the growing demands of modern networks and connected devices, but it imposes stringent requirements on transmitters, leading to potential reductions in efficiency due to high power usage. In this study, a highly efficient and linear CMOS power amplifier (PA) and up-conversion mixer were developed for 5G NR Sub-6GHz applications. A mixer-based linearizer was integrated at the PA's input to enhance performance across a wide frequency range, ensuring the system maintained high efficiency and linearity even with a 3 dB reduction in output power. The integrated CMOS PA and mixer, fabricated using 130 nm CMOS technology, cover a 1 GHz bandwidth from 4 GHz to 5 GHz. Measurement results demonstrated a gain of over 30 dB, with maximum output power ranging from 23.85 to 23.39 dBm, peak power-added efficiency (PAE) from 41.3% to 41.04%, and an output third-order intercept point (OIP3) between 31.38 and 32.53 dBm. The system's ability to maintain linearity was confirmed through testing with a 16 QAM signal, highlighting the innovation of the mixer-based linearizer integrated with the mixer before feeding into the PA.